2015
DOI: 10.14393/bj-v31n6a2015-28431
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and diversity of Ralstonia solanacearum populations in Brazil

Abstract: ABSTRACT:Ralstonia solanacearum is a gram-negative soil-borne bacterium capable of infection of hundreds of vegetable species over more than 50 botanical families, causing bacterial wilt, except for bananas, when the disease is called Moko. It deserves special attention, from all other plant pathogenic bacteria, for its high phenotypic and genotypic plasticity, a characteristic that makes disease control extremely difficult. In this context, frequent and necessary surveys are conduct in the attempt of characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
4
0
9
Order By: Relevance
“…Various findings have reported Ralstonia strains as differing in their virulence [45,46]. Morais et al [47] reported that information on the pathogenicity and molecular variability of Ralstonia strains will improve our knowledge on the epidemiology and ecology of these pathogens. This is particularly true with respect to latency, survival and aggressiveness of each strain.…”
Section: Influence Of Organic and Inorganic Soil Amendments On Diseasmentioning
confidence: 99%
“…Various findings have reported Ralstonia strains as differing in their virulence [45,46]. Morais et al [47] reported that information on the pathogenicity and molecular variability of Ralstonia strains will improve our knowledge on the epidemiology and ecology of these pathogens. This is particularly true with respect to latency, survival and aggressiveness of each strain.…”
Section: Influence Of Organic and Inorganic Soil Amendments On Diseasmentioning
confidence: 99%
“…Ralstonia solanacearum (SMITH, 1896) é o agente causal da murcha bacteriana (exceto quando acontece na bananeira, na qual é chamada Moko), uma das doenças mais destrutivas para muitas culturas importantes, e a principal doença vascular de etiologia bacteriana encontrada no mundo. Foi observada inicialmente em plantas de tabaco no Japão ao final do século 17 (KELMAN, 1953;MORAIS, 2015;GAMA et al, 2016;).…”
Section: Ralstonia Solanacearumunclassified
“…O gênero Ralstonia pertence à subdivisão beta das Proteobactérias, são bactérias Gram-negativas, em forma de bastonetes, se movimentam pela presença de um ou mais flagelos, estritamente aeróbicos, e capazes de produzir pigmento marrom difusível quando cultivadas in vitro (BRINGEL;UESUGI, 2001;AGRIOS, 2005). Quando cultivados em meio de cultura, os isolados virulentos formam colônias de coloração branca, retas, irregulares e fluídas, enquanto as formas não-virulentas são pequenas, circulares, não fluidas e de cor branco-creme (MORAIS, 2015).…”
Section: Ralstonia Solanacearumunclassified
See 2 more Smart Citations